THE POLITICAL IMAGING OF BOBBY AFIF NASUTION ON SOCIAL MEDIA IN WINNING THE 2024 NORTH SUMATRA GUBERNATORIAL ELECTION - Khairunnisa; Anang Anas Azhar (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the political image-building strategy employed by Bobby Afif Nasution through social media in his effort to win the 2024 North Sumatra gubernatorial election (Pilgub Sumut). Utilizing a qualitative approach, the research draws on data from observations of TikTok and Instagram content, interviews with active voters, and digital documentation collected during the campaign period. The analysis reveals that Bobby Nasution’s imaging strategy consists of four key aspects: personal branding, two-way interaction with the public, digital campaigning, and electability enhancement through positive narratives. This approach demonstrates the effective application of political and digital communication theories, evidenced by his consistent efforts to portray himself as a young, religious, and people-oriented leader. The strategy successfully shaped a positive public perception without employing negative narratives against political opponents, while strengthening emotional closeness with voters, particularly the younger generation. This study highlights the crucial role of social media as a primary channel for political communication in the context of modern electoral contests.